Counting by 7s - Sloan, Holly Goldberg, 1958- (Puffin Books, 2014)
When twelve-year-old genius Willow Chance loses her parents in an accident, her journey to find and accept a new family leads her through unexpected turns in life and forces her to confront reality in new ways.